Inisiasi Pendirian dan Pengelolaan Bank Sampah - Pribadi, Ulung; Aji, Juhari Sasmito; Widayat, Rossi Maunofa (Universitas Muhammadiyah Yogyakarta, 2021)
Environmental conservation is a shared responsibility for the government, private companies, and the community. One of the efforts to protect the environment is to pay attention to waste disposal. Household contribution to waste generation ranks first compared to other sectors. Therefore, efforts should be made to develop public awareness of waste management. The implementation of the service program aimed to build awareness and management of waste originating from household activities. The methods in the community service program were through tutorials and mentoring. The results of the program showed that the communityâ€™s more concerned and aware of the importance of waste management. The main indicator of improved community concern was the establishment of the â€œKluwih Resikâ€ Waste Bank.Â